The Canadian Women’s Heart Health Alliance ATLAS on the Epidemiology, Diagnosis, and Management of Cardiovascular Disease in Women — Chapter 7: Sex, Gender, and the Social Determinants of Health - Colleen M. Norris, PhD, GNP, MSc, BScN, FAHA, FCAHS; Kerri-Anne Mullen, PhD, MSc; Heather J.A. Foulds, PhD; Shahin Jaffer, MD, MHSc, FRCPC; Kara Nerenberg, MD, MSc; Martha Gulati, MD, MS, FACC, FAHA, FASPC, FESC; Nazli Parast, BScN, MN, CDE; Nicole Tegg, RN, BScN, MN; Christine A. Gonsalves, PhD; Jasmine Grewal, MD; Donna Hart, BA, RSW; Anna L.E. Levinsson, PhD; et al. (CJC Open, 2024)
Women vs men have major differences in terms of risk-factor profiles, social and environmental factors, clinical presentation, diagnosis, and treatment of cardiovascular disease. Women are more likely than men to experience health issues that are complex and multifactorial, often relating to disparities in access to care, risk-factor prevalence, sex-based biological differences, gender-related factors, and sociocultural factors. Furthermore, awareness of the intersectional nature and relationship of sociocultural determinants of health, including sex and gender factors, that influence access to care and health outcomes for women with cardiovascular disease remains elusive. This review summarizes literature that reports on under-recognized sex- and gender-related risk factors that intersect with psychosocial, economic, and cultural factors in the diagnosis, treatment, and outcomes of women’s cardiovascular health. Résumé: Les profils de facteurs de risque, les facteurs sociaux et environnementaux, le tableau clinique, le diagnostic et le traitement des maladies cardiovasculaires montrent des différences importantes entre les femmes et les hommes. Il est plus probable que les femmes expérimentent des problèmes de santé complexes et multifactoriels, qui sont souvent en relation avec les disparités dans l’accès aux soins, la prévalence des facteurs de risque, les différences biologiques entre les sexes, les facteurs liés au genre et les facteurs socioculturels. De plus, la sensibilisation à la nature et à la relation intersectionnelles des déterminants socioculturels de santé, notamment les facteurs liés au sexe et au genre, qui influencent l’accès aux soins et les résultats cliniques des femmes atteintes d’une maladie cardiovasculaire demeure insaisissable. La présente revue résume la littérature qui porte sur les facteurs de risque liés au sexe et au genre peu reconnus qui se recoupent aux facteurs psychosociaux, économiques et culturels dans le diagnostic, le traitement et les résultats cliniques en lien avec la santé cardiovasculaire des femmes.